Medieval imagery in today's politics - Wollenberg, Daniel (Past imperfect (ARC Humanities Press), 2018)
Though the "medieval" is often deployed as a stigmatic symbol of all that is retrograde, against modernity, and barbaric, the medieval is increasingly being sought as a bedrock of tradition, heritage, and identity, especially by writers and politicians on the far right. Both characterizations - the medieval as violent other and the medieval as vital foundation - are mined and studied in this book. Daniel Wollenberg examines contemporary political uses of the Middle Ages to ask why the medieval continues to play such a prominent role in the political and historical imagination today.